Two densities of extreme UV pellicle with enhanced properties
Patent Information
- Application Number
- JP2026516261
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-02
- Filing Date
- 2024-09-30
- Publication Date
- 2026-10-16
Smart Images

Figure 2026534442000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] Cross-Reference to Related Applications This application claims priority to U.S. Provisional Application No. 63 / 542,010 filed on October 2, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates generally to thin films and thin film devices used in advanced semiconductor microchip manufacturing, and more specifically, to patterned, dual-density, ultra-thin, ultra-low density, nanostructured free-standing pellicle films, as well as pellicles having improved mechanical properties and etching resistance properties, wherein the aforesaid films and film devices are configured for extreme ultraviolet (EUV) lithography and high numerical aperture (high NA) EUV.
BACKGROUND ART
[0003] Extreme ultraviolet (EUV) lithography is an advanced optical lithography technique that uses the EUV wavelength range, more specifically, a wavelength range of approximately 13.5 nm. EUV lithography enables semiconductor microchip manufacturers to pattern intricate features at resolutions of 14 nm or smaller, to arrange even more transistors without increasing the size of the substrate. For more sophisticated semiconductors of 7 nm, or even 5 nm or smaller, high NA EUV lithography has been developed and will be deployed for implementation in the semiconductor industry.
[0004] In EUV lithography, EUV radiation energy or high-level EUV radiation energy from high NA EUV lithography in the presence of low-pressure background hydrogen gas used for anti-oxidation and carbon cleaning in EUV lithography leads to ionization of hydrogen, generating reactive hydrogen plasma that reacts with plasma-facing surfaces including the surfaces of mirrors, photomasks, and pellicles. Such reactions alter the targeted properties of these components. In the case of mirrors, periodic inspection, cleaning, and even replacement may become necessary.
[0005] Particle contamination is another concern in EUV lithography. Field reports from the semiconductor industry indicate that despite the use of state-of-the-art cleanrooms and air filtration technologies, fallout on photomasks from known and unknown particle sources is still observed after photomask exposure in lithography. Such particle contamination, even in small amounts, is often a significant problem in semiconductor manufacturing, propagating incorrect patterns in the subsequent production of semiconductor chips. This problem is more pronounced in advanced photolithography for many high-resolution processes, as unexpected particles can alter the printed patterns of logic circuits on chips that lack built-in redundancy, thus increasing defect rates and impacting product yield.
[0006] To avoid particles, the photomask can be covered and protected by an effective pellicle, which is a thin transparent film stretched over a frame (also called a pellicle boundary with a central opening or aperture) that can be mounted on the pattern side of the photomask. The photomask is sometimes called a reticle. Both photomasks and reticles are now used interchangeably in semiconductor microchip manufacturing. The photomask is a master template for forming a pattern on a substrate, which is usually a thin slice of silicon known as a wafer in semiconductor chip manufacturing, by repeatedly irradiating the substrate with EUV light.
[0007] The pellicle is positioned close to the photomask but far enough away so that small particles falling onto it are far enough away that they do not focus in the print. The pellicle acts as a protective device covering the photomask, also called the reticle. When the EUV light source is turned on, the EUV light first hits the pellicle film and then passes through it. The EUV photomask beneath the pellicle reflects the light, bouncing it back from beneath the photomask and hitting the pellicle film again before continuing its path to print the microchip. During this process, some of the EUV energy is absorbed, and the double passage of EUV light can generate, absorb, and accumulate heat within the pellicle. The temperature of the pellicle can heat up to over 500°C to 1000°C. Therefore, heat resistance of the pellicle is essential.
[0008] While heat resistance is essential, the pellicle must also be highly transparent to EUV to ensure the passage of EUV light, reflected light, and the light pattern from the photomask. Increasing the pellicle film thickness to obtain film strength and heat resistance, or etching, can reduce EUV transmission, and the thicker film may become unsuitable for EUV lithography. This is one of the main reasons why EUV pellicles generally need to be very thin, with a thickness of less than 200 nm, preferably less than 100 nm, or less than 40 nm.
[0009] Attempts have been made to achieve high light transmittance by increasing the carbon nanotube content (e.g., reaching 99% by mass) in carbon nanotube sheets. These can form pellicles with high visible light and EUV transmittance. Ultrathin, ultra-low density CNT pellicle films have been reported to have satisfactory lifespans.
[0010] However, as pellicle films become thinner and thinner, the slow pump-down speed of EUV scanners can limit equipment availability and microchip manufacturing time, thus creating a high demand for better mechanical properties of the pellicle film. Furthermore, the space between the pellicle film and the reticle remains small and limited, thus creating a widespread need to reduce pellicle film deformation.
[0011] EUV radiation-induced hydrogen plasma also affects the pellicle in addition to reflective mirrors, and hydrogen ionization and reactive hydrogen plasma, i.e., hydrogen plasma etching, strike the pellicle, resulting in defects within the pellicle film and shortening its lifespan.
[0012] In the microchip manufacturing industry, EUV pellicles have already been adopted, and promising initial results have been shown in reducing print defects and improving production yield. Therefore, there remains a strong demand for EUV pellicles for high-energy power EUV lithography or high-NA EUV lithography, particularly pellicles with improved heat resistance, mechanical strength, and hydrogen plasma etching resistance. For EUV pellicles, their mechanical strength within the scanner, film integrity, particle prevention capability, and lifespan are critical and play a vital role in EUV lithography. If they are damaged, broken, or even disintegrate, they not only lose their protective function but also produce fragments of the broken pellicle, which can cause additional damage and / or contamination to the scanner, scanner module, and the scanner's internal environment. [Overview of the Initiative]
[0013] According to aspects of this disclosure, a specifically structured nanostructured film is disclosed. The nanostructured film comprises a plurality of carbon nanotubes (or carbon nanofibers) randomly intersecting to form a monolayer of interconnected nanofiber network structures having a geometric shape and a target size for planar orientation to at least one surface of the interconnected nanofiber network structure. Furthermore, the intersecting or interconnected nanofiber network structures have a plurality of carbon nanotubes continuously dispersed or distributed throughout the intersecting network and a pattern of at least two light transmittances, i.e., one light transmittance being higher than the other. For example, the at least two light transmittances may include a high or higher light transmittance and a low or lower light transmittance. Exemplary light used in light transmittance measurements includes, for example, visible light at 550 nm and, for example, EUV light at 13.5 nm, but is not limited to these.
[0014] According to another aspect of the present disclosure, the intersecting network structure may have at least two thicknesses selected from a range of a lower limit of 3 nm to an upper limit of 200 nm. Thicker regions of the interconnected nanofiber network structure have lower visible light transmittance or lower EUV transmittance (i.e., lower EUV transmittance), and thinner regions of the interconnected nanofiber network structure have higher visible light transmittance or higher EUV transmittance (i.e., higher EUV transmittance).
[0015] According to yet another aspect of this disclosure, thicker regions of the network structure of interest may have a higher area density of multiple intersecting nanofibers, while thinner regions of the interconnected network structure may have a lower area density of multiple intersecting nanofibers.
[0016] According to one aspect of this disclosure, the visible light transmittance is selected from a range between a lower limit of 40% and an upper limit of 97% measured at a wavelength of 550 nm for at least two different transmittances.
[0017] According to further aspects of this disclosure, the interconnected nanofiber network structure may have at least two EUV transmittances selected from or measured within a range between a lower limit of 80% and an upper limit of 99%, measured at a wavelength of 13.5 nm.
[0018] According to another aspect of this disclosure, the high transmittance of both visible and / or EUV wavelengths is at least 2% and up to 50% higher than the low transmittance.
[0019] According to one aspect of this disclosure, the interconnected nanofiber network structure has a geometric shape having a target size. A preferred geometric shape is rectangular, and a preferred target size is a rectangle of 110 mm × 140 mm, which meets current standards for EUV pellicles. This disclosure is not limited to the shapes and sizes of the interconnected nanofiber network structures disclosed herein. Further, geometric shapes such as triangles, squares, circles, ellipses, heptagons, and octagons may be included. The size of the interconnected nanofiber network structure may be larger than 110 mm × 140 mm, such as 120 mm × 150 mm or more, 130 mm × 160 mm, 110 mm × 280 mm, 220 mm × 140 mm or more. The size of the interconnected nanofiber network structure may be smaller than 110 mm × 140 mm, such as 25 mm × 25 mm, 20 mm × 20 mm, or 10 mm × 10 mm.
[0020] At least two preferred patterns of light transmittance for an interconnected nanofiber network structure include lower light transmittance in the peripheral region of the rectangle of the interconnected nanofiber network structure and higher light transmittance in the central region of the rectangle of the interconnected nanofiber network structure.
[0021] Furthermore, preferred patterns of light transmittance for at least two interconnected nanofiber network structures include lower light transmittance from one or more areas around the periphery of a given geometric shape of the interconnected nanofiber network structure to the entire periphery, and higher light transmittance in the central region of the given geometric shape of the interconnected nanofiber network structure.
[0022] A preferred pattern may further include a transition region between the peripheral and central regions of the intersecting nanofiber network structure. The transition region may have variable light transmittance. A preferred variation of the light transmittance of the transition region is a gradient of light transmittance from low to high, i.e., lower light transmittance where the transition region is coupled with the peripheral region and higher light transmittance where it is coupled with the central region.
[0023] Another embodiment of the present disclosure further includes a width of the peripheral region selected from any measurement between a lower limit of 0.2 mm and an upper limit of 4.0 mm. The width may be 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, or 3.5 mm.
[0024] One embodiment of the present disclosure includes an interconnected nanofiber network structure (i.e., a first pellicle film having a central region, a transition region, and a peripheral region) having reduced deflection compared to a separated interconnected nanofiber network structure, wherein the separated interconnected nanofiber network has a uniform light transmittance corresponding to the light transmittance of the central region of the first pellicle film.
[0025] Another embodiment of the present disclosure further includes the aforementioned interconnected nanofiber network structure (first pellicle film) having greater deflection compared to yet another interconnected network structure (third pellicle film) having a uniform light transmittance corresponding to the light transmittance in the peripheral region of the first pellicle film.
[0026] Another embodiment of the present disclosure further comprises a first interconnected nanofiber network structure, wherein the first interconnected nanofiber network structure has at least two non-identical light transmittances (i.e., a higher light transmittance and a lower light transmittance), preferably having a pattern (at least a central region with a higher light transmittance and a peripheral region with a lower light transmittance), and this pattern has less deflection of the interconnected nanofiber network structure compared to a second interconnected nanofiber network structure with a uniform light transmittance that is the higher light transmittance of the at least two non-identical light transmittances, and greater deflection of the interconnected nanofiber network structure compared to a third interconnected nanofiber network structure with a uniform light transmittance that is the lower light transmittance of the at least two non-identical light transmittances, and has the aforementioned at least two non-identical light transmittances, and the same EUV transmittance of one region, i.e., the central region of the first interconnected nanofiber network structure, as compared with the EUV transmittance of the second interconnected nanofiber network structure.
[0027] Another embodiment of the present disclosure comprises a plurality of carbon nanofibers, wherein the plurality of carbon nanofibers has at least 50% double-walled carbon nanotubes, at least 50% single-walled carbon nanotubes, or at least 50% multi-walled carbon nanotubes having carbon nanotubes with three or more walls, and the remaining portion is filled with carbon nanofibers including carbon nanotubes having different numbers of walls other than those already specified, ultimately accounting for 100% of the content.
[0028] Another embodiment of the present disclosure comprises a plurality of nanofibers, wherein the plurality of nanofibers has at least 50% double-walled carbon nanotubes, 20% to 40% single-walled carbon nanotubes, and a remaining portion filled with multi-walled carbon nanotubes (i.e., carbon nanotubes with three or more walls), ultimately accounting for 100% of the content.
[0029] Another embodiment of the present disclosure includes a plurality of nanofibers, where the plurality of nanofibers has a remaining portion filled with at least 50% up to 75% double-walled carbon nanotubes, at least 20% up to 40% single-walled carbon nanotubes, and at least 1% carbon nanotube members with three or more walls (multi-walled CNTs), ultimately accounting for 100% of the content.
[0030] According to one aspect of the present disclosure, a pellicle is disclosed. The pellicle includes a pellicle boundary or pellicle frame having an aperture, and at least one interconnected nanofiber network structure (also referred to as a pellicle film) mounted on the pellicle boundary to cover the aperture.
[0031] According to one aspect of the present disclosure, a method for manufacturing a pellicle film or pellicle device for EUV lithography is disclosed. An exemplary method includes the steps of producing a pellicle film having at least two non-identical light transmittances in two corresponding regions of the pellicle film, preferably by a filtration method, mounting the pellicle film on a pellicle boundary to form a pellicle or an intermediate boundary, and optionally moving the pellicle film from the intermediate boundary onto the pellicle boundary to form a pellicle, which may also be referred to as a pellicle device.
[0032] According to another aspect of the present disclosure, the method further includes the step of obtaining a plurality of randomly intersecting carbon nanofibers to form a single layer of an interconnected nanofiber network structure. The plurality of carbon nanofibers has a central region and a peripheral region, and is continuously distributed throughout the single layer of the interconnected nanofiber network structure that intersects from one of the central region and the peripheral region to the other region.
[0033] According to another aspect of the present disclosure, the method further includes the step of manufacturing a central region of the pellicle film as one of the two non-identical light transmission regions, and a peripheral region of the pellicle film as the other one of the two non-identical light transmission regions.
[0034] According to yet another aspect of this disclosure, the method further includes making the light transmittance of the central region higher than that of the peripheral region. One of these two light transmittances is at least 5% higher than the other, preferably 10%, 15%, 20%, 25%, 30%, 40%, or 50% higher than at least one of the selected wavelengths, such as 550 nm in the example of visible light and 13.5 nm in EUV.
[0035] According to another aspect of the present disclosure, a method for manufacturing a pellicle film or pellicle device for EUV lithography further comprises a third region of the pellicle film, the third region being located between and integrated with two regions having non-identical light transmittances. The description of integration refers to the random intersection of multiple carbon nanofibers, as well as the continuous distribution of multiple carbon nanofibers within all three regions, and the crossing from one of the three regions to another. The third region preferably has a progressive pattern of varying light transmittances, changing from one of the two non-identical light transmittances to the other.
[0036] Another aspect of this disclosure discloses a method for performing EUV lithography, comprising at least one of the steps disclosed herein.
[0037] This disclosure is further described in the following detailed description with reference to several drawings which are referred to as non-limiting examples of preferred embodiments of this disclosure, and similar letters throughout several of the drawings represent similar components. [Brief explanation of the drawing]
[0038] [Figure 1] An exemplary embodiment illustrates a filtration method for forming an interconnected nanofiber network structure. [Figure 2]This is a schematic diagram of a top view of an interconnected nanofiber network structure having a geographical shape, size having length and width, and three regions within the geographical shape, according to an exemplary embodiment. [Figure 3] Another schematic diagram of a top view of an interconnected nanofiber network structure having a geographic shape, size having length and width, and three regions within the geographic shape mounted on a pellicle frame, according to an exemplary embodiment. [Figure 4] Figure 2 is a schematic side view of an interconnected nanofiber network structure, which, according to an exemplary embodiment, has multiple nanofibers continuously dispersed throughout the interconnected nanofiber network structure shown. [Figure 5] The following shows deflection measurements under various test pressures obtained from three full-size individual interconnected nanofiber network structures mounted on a boundary having an aperture of 110 mm × 140 mm, according to an exemplary embodiment. [Figure 6] The results of deflection and burst tests from three individual interconnected nanofiber network structures according to exemplary embodiments are illustrated. [Figure 7] For each interconnected nanofiber network structure measured at 550 nm with and without hydrogen plasma etching, we illustrate the burst test results from two sets of interconnected nanofiber network structures with one or two light transmittances. [Modes for carrying out the invention]
[0039] Through one or more of these various embodiments, embodiments and / or specific features, subcomponents, or processes of the present disclosure are intended to illustrate one or more of the advantages specifically mentioned above and referred to below.
[0040] A pellicle can refer to a thin, transparent film that protects a photomask during semiconductor microchip manufacturing. The pellicle envisions a protective device comprising a frame (also called a boundary, used interchangeably herein) with a central opening, aperture, or window. Both the boundary and aperture are covered by a continuous thin, transparent film over at least a portion of the boundary and the portion of the aperture, preferably around the entire perimeter of the boundary and over the entire aperture. The central portion of such a thin film extending into the aperture is freestanding. The pellicle can function as a fine powder cover or filter that prevents particles and contaminants from falling onto the object(s) beneath the pellicle. In extreme ultraviolet (EUV) lithography, an EUV pellicle refers to a particle filter or particulate filter for protecting the photomask and other objects in the non-semiconductor field during microchip manufacturing. However, the pellicle must be sufficiently transparent to allow the light necessary for lithography to pass through it. Higher light transmittance is desirable for more effective lithography. For most EUV lithography applications, an EUV transmittance of 80% from the pellicle may be acceptable. For high-resolution EUV lithography of 7nm or less, high-energy EUV scanners, or high numerical aperture or ultra-high numerical aperture EUV lithography, preferred EUV pellicles may require an EUV transmittance of 90% or higher, 92% or higher, or 95% or higher, and up to 99%.
[0041] Furthermore, pellicles for EUV lithography require large (e.g., 110mm x 140mm or larger), self-supporting, thin film materials with extreme and specific properties. In addition to high permeability to EUV irradiation, any unexpected film rupture during microchip production can disrupt the ongoing manufacturing process, potentially leading to scanner debris decontamination, photomask replacement or cleaning, and loss of microchip production. Film rupture can be caused by impacts during pellicle transport and / or changes in environmental pressure. It can also occur due to low mechanical strength of the pellicle film, reduced mechanical strength, and / or short or reduced pellicle film life resulting from scanner pressure changes (i.e., pump-down or venting) and / or hydrogen plasma etching within the scanner.
[0042] Because EUV is absorbed by most substances, including common gases and the atmosphere, EUV lithography is performed in a vacuum. Therefore, direct irradiation of the pellicle film with EUV radiation can rapidly heat it. The absorbed energy cannot be rapidly and reliably released or removed by conventional cooling methods such as convection and conduction cooling. The temperature of the pellicle film can rapidly reach several hundred degrees Celsius or more within the scanner, for example, above 400°C, 600°C, 800°C, 1000°C, and even above 1200°C. Such high temperatures can have adverse effects, degrading materials containing carbon nanofibers and carbon nanotubes, ultimately weakening the mechanical strength of the interconnected nanofiber network structure and shortening its lifespan.
[0043] Furthermore, EUV lithography requires a low-pressure hydrogen stream to sweep away particles that could contaminate the precision scanner mirror, providing antioxidant and carbon cleaning functions to protect the EUV mirror surface and other surfaces inside the scanner. When high-energy EUV radiation is present inside the scanner, the hydrogen gas undergoes ionization, generating a very high-temperature hydrogen plasma, which releases particles that corrode the reticle, pellicle, and adjacent surfaces such as the reticle surface and the pellicle surface. This hydrogen plasma etching presents another serious challenge for all EUV pellicles. To achieve high-temperature resistance, extended pellicle life, and high plasma etching requirements, high-quality EUV pellicle films with better mechanical strength, less film deflection, and high etching resistance may be required. Given the number of high-level properties required, effective EUV pellicles, especially for high-NA EUV lithography, have traditionally been difficult to manufacture to meet very stringent standards.
[0044] In this embodiment, carbon nanotubes and other equivalent nanofibers are selected as starting materials for generating pellicles for this EUV pellicle application due to their excellent thermal and mechanical properties, as well as their ability to form porous films. Additional details of the pellicle film structure can be crucial in overcoming the serious challenges of EUV and high-NA EUV lithography.
[0045] Carbon nanotubes and carbon nanotube films Carbon nanotubes (CNTs) or carbon nanofibers, as frequently referred to herein, are typically long tubes with small diameters measured in nanometers. They have a high aspect ratio of diameter to length, generally preferably exceeding about 100:1, and sometimes exceeding about 1000:1. Another preferred aspect ratio may be at least about 10,000:1. CNTs consist of one or more concentrically wound graphene sheets. A graphene sheet is an aggregate of carbon allotropes arranged in a single layer with a hexagonal crystal structure. Each graphene sheet is considered a wall of the CNT. Single-walled CNTs (SWCNTs) are formed from one graphene sheet. Double-walled CNTs (DWCNTs) are formed from two graphene sheets. Finally, multi-walled CNTs (MWCNTs) have multiple graphene sheets. Multi-walled CNTs, as used herein, refer to carbon nanotubes having three or more walls. Other types of CNTs may include, but are not limited to, coaxial nanotubes, conical carbon nanotubes, closed-loop carbon nanotubes, boron nitride nanotubes, and composite coaxial nanotubes of graphene layers(or more) and boron nitride layers(or more). Other carbon allotropes may also form sheets with excellent properties as pellicle films. Carbon nanotubes may exist as substantially pure single types, or often in combination with other types for a given number of CNT walls. CNTs may also exist individually, separated from others, or they may form bundles. Bundles may contain CNTs of the same type or different types, such as SWCNTs with DWCNTs, SWCNTs with MWCNTs, DWCNTs with MWCNTs, etc. Within a bundle, CNTs may have different lengths and diameters. Each bundle containing two or more CNTs may be aligned in parallel for at least a portion of its total length. For simplification and convenience, CNTs in this application may mean different types of CNTs, e.g., different numbers of walls, and may include CNTs that exist individually or in bundles.
[0046] As used herein, nanofibers may, in exemplary terms, mean fibers with a diameter of less than 1 μm. Nanofibers and nanotubes are used synonymously and may include SWCNTs, DWCNTs, MWCNTs, and other carbon allotropes in which carbon atoms bond to each other to form a cylindrical structure.
[0047] Individual CNTs or CNT bundles may intersect with one or more other CNTs or CNT bundles. Many CNTs together can form a mesh-like microstructure film. One exemplary embodiment may include a self-supporting thin film of interconnected nanofibers or carbon nanofiber network (micro)structures, in which there is no support material or substrate on either side of the self-supporting thin film in the region of the thin film.
[0048] Furthermore, among several possible methods for manufacturing self-supporting thin films, a filtration-based approach is used to produce film ranging from small-sized films to sufficiently large films with uniform film thickness for EUV lithography having at least two regions, where each film has uniform film thickness or uniform light transmittance for each of the at least two regions. Uniform film thickness generally correlates with uniform light transmittance. This filtration-based method enables the rapid production of films of other high aspect ratio nanoparticles and nanofibers, such as boron nitride nanotubes (BNNTs) or silver nanowires (AgNWs), as well as CNT films. Because this approach separates the synthesis of nanotubes or nanoparticles from the film manufacturing process, various nanofiber materials produced by virtually any method can be used individually or in combination. Different types of nanotubes (SWCNTs, DWCNTs, MWCNTs, or carbon allotropes) can be mixed in any desired ratio. Filtration can be a self-leveling process in the sense that non-uniformity of film thickness during the filtration process is self-corrected by local variations in permeability, and therefore can be a highly desirable film formation process and a promising candidate for the production of highly uniform films. The self-leveling process can further ensure that nanoparticles or nanofibers are uniformly dispersed and deposited in an orderly and uniform manner under the same filtration conditions.
[0049] Synthesis of carbon nanotubes Carbon nanofibers can be synthesized by different methods depending on the desired product type. These methods involve different precursors, such as hydrocarbon gases, heat sources, reaction catalysts, reaction times, reaction temperatures, and reaction atmospheres. The most common methods include, but are not limited to, arc discharge, electrolysis, laser ablation, chemical vapor deposition (CVD), flame synthesis, and mechanothermal processes. Well-known CVD methods have evolved to include plasma-enhanced PE-CVD, aerosol CVD (AACVD), water-assisted WA-CVD, oxygen-assisted CVD, and catalytic CVD.
[0050] These CNT production methods utilize one or more carbon sources, such as acetylene (C2H2), ethylene (C2H4), or other hydrocarbons, in a closed reaction chamber with at least one catalyst, at a heated reaction temperature range of 350 to 1,000°C or higher.
[0051] During synthesis in a CVD reaction chamber (FC-CVD), the catalyst may be suspended within the reaction chamber. FC-CVD is applied under the thermal decomposition of hydrocarbon gas(s) to produce nanofiber sheets. Alternatively, FC-CVD can produce nanofibers under different growth conditions, and as described later, the nanofibers can be collected as CNT powder for subsequent dispersion and filtration to produce pellicle films.
[0052] Other commonly employed CVD synthesis methods begin with catalyst deposition on substrates such as silicon wafers using electron beam (E-beam) deposition, sputtering, atomic layer deposition, laser-assisted CVD, and plasma CVD. Aggregates of individual nanofibers align perpendicularly to each other on the substrate, often referred to as CNT forests, with one end of each nanofiber attached to the substrate. These can be separated from the substrate and recovered as CNT powder for the production of CNT pellicle films.
[0053] Film formation Ultra-thin and ultra-low-density CNT pellicle films can be manufactured according to exemplary embodiments of the present disclosure.
[0054] Figure 1 illustrates a filtration method for forming the pellicle film shown in Figures 2 to 4, according to an exemplary embodiment.
[0055] Another embodiment of the present disclosure may further include any pellicle film manufactured, manufactured, processed, or to be processed by any means including, but not limited to, the deposition, annealing, or combination thereof of one or more metal elements, metal oxides, graphene sheets, or CNT surface modifiers on carbon nanofibers and / or CNT films by coating or other means.
[0056] As illustrated in Figure 1, a self-supporting carbon nanotube-based pellicle film can be manufactured by a filtration-based method. In operation 101, the catalyst is removed from the carbon nanotubes (CNTs) used to form an aqueous suspension. In one example, before dispersion in the suspension, the CNTs can be chemically purified to reduce the concentration of catalyst particles to less than 1% by weight, or preferably less than 0.5% by weight, and these purified CNTs can be measured, for example, by thermogravimetric analysis. The removal of the catalyst is not limited to any particular process or procedure, and any suitable process may be used to achieve the desired result.
[0057] In operation 102, an aqueous suspension is prepared using purified CNTs so that the purified CNTs are uniformly dispersed in the aqueous suspension. When preparing one or more CNT suspensions, the carbon nanotube material is mixed with a selected solvent so that the nanotubes can be uniformly dispersed in the final solution as a suspension. Mixing may include mechanical mixing (e.g., using an electromagnetic stirring rod and stirring plate), ultrasonic stirring (e.g., using an immersion ultrasonic probe), or other methods. In some examples, the solvent may be a protic or aprotic polar solvent such as water, isopropyl alcohol (IPA), and aqueous alcohol mixtures, for example, 60%, 70%, 80%, 90%, 95% IPA, N-methyl-2-pyrrolidone (NMP), dimethyl sulfide (DMS), and combinations thereof. In other examples, a surfactant may be included to facilitate the uniform dispersion of carbon nanofibers in the solvent. Examples of surfactants include, but are not limited to, anionic surfactants.
[0058] Carbon nanofiber films are generally formed from one of MWCNTs, DWCNTs, or SWCNTs. Carbon nanofiber films may also contain mixtures of different types of CNTs (i.e., SWCNTs, DWCNTs, and / or MWCNTs based on the number of CNT walls) in varying ratios between different types of CNTs. CNT films can also be produced using other types of CNTs by filtration or other known and well-considered methods.
[0059] These three different types of common carbon nanotubes (e.g., MWCNTs, DWCNTs, and SWCNTs) each possess distinct properties. For example, single-wall carbon nanotubes can be more favorably dispersed in a solvent for subsequent formation into sheets of randomly oriented and intersecting carbon nanotubes (i.e., most of the nanotubes are suspended separately, resulting in less adsorption onto other nanotubes). The ability to uniformly disperse individual nanotubes in a solvent and / or solution allows for the production of more planarly uniform nanotube films formed by removing the solvent from suspended nanofibers. Dispersion uniformity in solution ensures a uniform distribution of the aggregate of individual nanotubes. This physical uniformity can also improve the uniformity of other properties of the film as a whole (e.g., transparency and scattering to irradiation, mechanical strength under pressure changes, and lifetime / durability testing).
[0060] In one example, the aqueous CNT suspension in operation 102 may have SWCNTs with a purity of at least 85% or more. The remainder may be a mixture of DWCNTs, MWCNTs, and / or a catalyst. In other examples, dispersed CNT suspensions can be prepared containing different types of CNTs in various ratios, such as approximately 20% / 75% DWCNT / SWCNT, approximately 50% / 45% DWCNT / SWCNT, and approximately 70% / 20% DWCNT / SWCNT, with MWCNTs making up the remainder. Mixtures of DWCNTs and SWCNTs blended in various DWCNT / SWCNT percentage ratios with more than 10% MWCNTs can be prepared and subjected to the same filtration process to form nanofiber structures. In another example, anionic surfactants can be used as dispersants in the suspension to enhance the uniform dispersion of different types of CNT mixtures.
[0061] In operation 103, the CNT suspension is further purified to remove aggregated or agglomerated CNTs from the initial mixture. In one example, different forms of CNTs (well dispersed compared to undispersed or aggregated) may be separated from the suspension by centrifugation. Centrifugation of carbon nanotubes suspended with a surfactant may help reduce the turbidity of the suspension solution and ensure complete dispersion of the carbon nanotubes in the final suspension solution before proceeding to the next filtration step. However, embodiments of this disclosure are not limited thereto, and other separation methods or processes may be used. According to exemplary embodiments, operation 103 may be performed optionally or as a required step in the formation of a pellicle film.
[0062] In operation 104, any CNT suspension, preferably the CNT supernatant after the separation procedure from operation 103, is then filtered through a filtration membrane to form a CNT nanostructure film, which is a continuous sheet of intersecting CNTs.
[0063] In one example, one technique for creating a CNT film involves using water or other fluids to arrange nanotubes on a filter, preferably a flat filtration membrane, in a random dispersion pattern. The uniformly dispersed CNT-containing mixture is passed through or forced through the filter, leaving a nanofiber structure layer on the filter surface where the dispersed CNTs intersect and interconnect. The size and shape of the resulting film are determined by the desired size and shape of the filter's filtration area, while the film's thickness and density are determined by the amount of nanofiber material applied during the filtration process and the permeability of the filtration membrane to each component of the input material, since non-permeable components are trapped on the filter's surface. If the concentration of nanofibers dispersed in the flow-through filtration fluid is known, the mass of nanofibers deposited on the filter can be determined from the amount of such fluid passing through the filter, and the surface density of the film can be determined by dividing the nanofiber mass by the total filtration area. The filtration area of the filter may be equal to or smaller than the size of the filter, depending on the underlying support structure of the filter. The selected filter is usually not permeable to any CNTs.
[0064] The filtered CNT film may be a combination of SWCNTs, DWCNTs, and / or MWCNTs in different compositions. Carbon nanofibers can be randomly intersected and interconnected to form a thin CNT film in the form of a nanofiber network structure. The first surface of the interconnected nanofiber network structure in contact with the filter membrane is planar oriented. The opposite surface of the interconnected nanofiber network structure has a planar orientation parallel to the first surface, which can produce a film with a single CNT surface density or a single light transmittance.
[0065] The opposite side of the interconnected nanofiber network structure may have a different planar orientation with respect to the planar orientation of the first surface, characterized by different light transmittances of the interconnected nanofiber network structure, as detailed below.
[0066] In operation 105, the obtained CNT film is then separated from the filtration membrane, starting from the first edge of the CNT film and moving toward the second edge, peeled from the first edge by different mechanisms and methods, for example, different hydrophobic / hydrophilic between the nanofiber film and the filtration membrane, with a soft water flow targeting the first edge. Once completely separated from the filtration membrane, the nanofiber film is ready for the next operation, operation 106.
[0067] In operation 106, the separated CNT film is recovered on a solid substrate, such as a frame sometimes called a recovery frame, recovery frame, or intermediate frame, depending on the desired subsequent operation and use of the CNT film. The separated CNT film may be recovered directly or mounted on the pellicle boundary with a defined aperture.
[0068] In operation 107, the CNT films can be characterized through various measurements, which may be performed by, but are not limited to, optical light transmission (or transmittance) and / or transmission uniformity (or transmission variation) tests, EUV transmission (or transmittance) and / or transmission uniformity (or transmission variation) tests, mechanical strength, deflection tests, permeability tests, deflection under constant pressure or under simulated scanner pumping-down conditions, lifetime tests, and particle tests.
[0069] In operation 107, the CNT film may be annealed, coated, or tension-adjusted.
[0070] Carbon nanotube film with two light transmittances Multiple carbon nanofibers or carbon nanotubes manufactured by different methods can be crossed between individual nanofibers and / or nanofiber bundles to form a single layer of interconnected nanofiber network structures, as schematically shown in Figures 2-4. Methods for producing interconnected nanofiber network structures include, but are not limited to, filtration methods. Single-layer interconnected nanofiber network structures produced by filtration methods may have different, or even random, light transmittances, as measured by one or more selected wavelengths. Single-layer interconnected nanofiber network structures produced by filtration methods may have variations in film thickness. Thickness generally correlates with light transmittance. Many factors can affect the resulting film thickness, including the permeability of the filtration membrane as a whole or in part, the post-filtration vacuum pressure applied to part or in part of the filtration membrane, the pre-filtration pressure applied to part or in part of the filtration membrane, and the filtration rate in part or in part of the filtration membrane. A combination of one or more of these control factors can result in the fabrication of films with different film area densities and / or different light transmittances (different transmittances), while the self-leveling of carbon nanofibers or carbon nanotubes allows for the continuous uniform deposition of carbon nanofibers or carbon nanotubes under the same set of control factors, enabling a smooth transition from the first set of control factors to the second set of control factors for carbon nanofiber or carbon nanotube deposition. Such combinations enable one-step film fabrication, avoiding the attachment of two non-identical layers and forming a film with two different densities or light transmittances, which has an interface between the two non-identical layers, further generating wrinkles and / or folds. Wrinkles, folds, fine wrinkles, or fine folds can all affect EUV radiation projection in semiconductor fabrication. The cross-sectional film microstructure may show an overall uniform surface density and distribution of carbon nanofibers or carbon nanotubes.
[0071] Another embodiment of the present disclosure includes a method for producing two films of different light transmittances based on a floating catalytic chemical vapor deposition (FC-CVD) method. The method includes injecting or placing at least one catalyst into a vacuum chamber; floating at least one catalyst in the vacuum chamber; providing at least one gas(s) (i.e., hydrocarbon gas(s)) as a carbon source; heating the vacuum chamber to thermally decompose at least one gas(s) for synthesizing carbon nanofibers or carbon nanotubes on the floating catalyst in the vacuum chamber; and depositing or trapping carbon nanotubes on filter paper or a filter film to form an interconnected and / or intersecting carbon nanotube film. The method may include a first carbon nanotube deposition for producing a pellicle film having one layer (i.e., a single-layer pellicle film) on the filter film. The method may further include one or more subsequent carbon nanotube depositions on the opening side of the carbon nanotube film to produce two or more layers of pellicle film (multilayer pellicle film). The opening side of the carbon nanotube film is opposite the filter film. Following one of the first carbon nanotube depositions or subsequent carbon nanotube depositions, a single-layer or multi-layer pellicle film can be transferred to a pellicle frame or pellicle intake frame, with the opening side interfaced with the pellicle frame or pellicle intake frame. The filter film is peeled off or removed. The single-layer or multi-layer pellicle film on the pellicle frame or pellicle intake frame can accept the deposition of one or more carbon nanotubes as described herein. At least one of the first and subsequent carbon nanotube depositions may additionally include the application of dampers or blockers to restrict the deposition of carbon nanotubes in part of the filter film or in part of the (single-layer or multi-layer) carbon nanotube film, producing a film having at least one layer having at least two light transmittances in a pre-selected pattern, including the patterns(s) shown in Figures 2-4.The damper may be applied to the entire duration or fragments of at least one of the first and subsequent carbon nanotube depositions that generate a pre-selected pattern. Carbon nanotubes within the carbon nanotube deposition may be sequentially trapped by the filter film or one of the subsequent carbon nanotube depositions and uniformly distributed within the cross-sectional microstructure.
[0072] One of the two film surfaces in contact with the filtration membrane forms a first planar orientation. The other of the two surfaces may have several surface planar orientations depending on different film area densities or different light transmittance values. For example, a film having a central region with high transmittance or low area density, a peripheral region with low transmittance or high area density, and a transition region connecting both the central and peripheral regions and having a transmittance gradient from low transmittance when connected to the peripheral region to high transmittance when connected to the central region has three surface regions. All three regions share one common surface planar orientation in contact with the filtration membrane from filtration. The second surface of the central region has a planar orientation opposite to the common surface planar orientation and is parallel to the second surface of the peripheral region. However, the second surface of the transition region, which is opposite to the common surface planar orientation, may not be parallel to the second surface of the peripheral region and may not be parallel to the second surface of the central region. Multiple nanofibers in an interconnected nanofiber network are not separated or demarcated by any of these regions. Instead, multiple nanofibers are randomly dispersed throughout the entire film, resulting in films with different area densities or varying light transmittances. These features and associated fine structural properties, along with the additional experimental results below, contribute to the enhancement of the nanofiber network structure.
[0073] The interconnected nanofiber network structure may have any geometric shape, including but not limited to squares, rectangles, circles, ellipses, heptagons, or octagons, with varying lengths, widths, and / or diameters.
[0074] Interconnected nanofiber network structures for EUV lithography may preferably be rectangular, with a target size of 110 mm × 140 mm covering a rectangular aperture. The interconnected nanofiber network structures can extend from 1 mm to 40 mm in any dimension, resulting in a size range of 111 mm to 150 mm × 141 mm to 170 mm. Different sizes covering a rectangular aperture, such as 10 mm × 10 mm, 20 mm × 20 mm, 120 mm × 150 mm, 220 mm × 140 mm, and 110 mm × 280 mm, or other variations, are conceivable.
[0075] For EUV lithography, interconnected nanofiber network structures can be very thin, ranging from a minimum of 3 nm to a maximum of 200 nm, or even from a minimum of 3 nm to a maximum of 100 nm, to ensure sufficient EUV transmittance. EUV pellicle films require a film, or more specifically, a portion of the film through which EUV passes, limiting variations in thickness or light transmission.
[0076] However, the ultra-thin film requirements and uniform thickness present the challenge of fabricating interconnected nanofiber network structures with sufficient mechanical strength to withstand human handling, transport, or air transport, as well as the pump-down and aeration processes of EUV scanners, and pressure changes during radical or ionization attacks. Selecting one or more types of nanofibers in terms of the number and structural layout of carbon nanotube walls is one practical approach.
[0077] One embodiment of the present disclosure includes a modification of the peripheral region of an interconnected nanofiber network structure. When mounted or attached to a support frame or pellicle frame, the interconnected nanofiber network structure may be divided, firstly, into a freestanding portion without support or a freestanding portion covering the aperture of the pellicle frame, and secondly, into a non-freestanding portion surrounding the freestanding portion on the support frame or pellicle frame and extending outward from the freestanding portion. The peripheral region of the mounted interconnected nanofiber network structure may refer to the outside or periphery of the freestanding portion of the interconnected nanofiber network structure as described herein, and this may represent one of the exemplary embodiments of the present disclosure and its ability to improve the functionality of the interconnected nanofibers illustrated below. The peripheral region of the mounted interconnected nanofiber network structure may further include a non-freestanding mounted portion of the interconnected nanofiber network structure.
[0078] Peripheral regions of an interconnected nanofiber network structure with lower light transmittance relative to its geometric shape may have different parts or areas within the peripheral region that have different lower light transmittance relative to the high light transmittance of the non-peripheral region (i.e., the central region). An exemplary rectangular peripheral region of an interconnected nanofiber network structure with lower light transmittance may include one side of the rectangle (i.e., one straight section of the peripheral region), two sides, three sides, or all four sides of the rectangle. Feature 210 in Figure 2 shows a closed peripheral region having four connected straight sections of the peripheral region. The peripheral region may include two sides of the rectangle, i.e., the first and second sides, where the first side is opposite the second side. In this example, the peripheral region has two unconnected straight sections.
[0079] Another embodiment of the present disclosure further includes the width of the peripheral region. The width may be the same or different across all parts or areas of the peripheral region. For example, the four sides of the peripheral region of an exemplary rectangle may have one or two widths, with the first width covering two opposing long sides and the second width covering two opposing short sides. The width may be selected from any measurement between a lower limit of 0.2 mm and an upper limit of 4.0 mm. The width may be 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, or 3.5 mm. A width less than 0.2 mm may not provide the benefits provided by any embodiment of the present disclosure. A width wider than 4.0 mm can effectively reduce the usable area of the film, such as the central region, for EUV irradiation.
[0080] One embodiment of the present disclosure further comprises a plurality of nanofibers having at least 50% double-walled carbon nanotubes. The remainder are filled with single-walled and / or multi-walled carbon nanotubes, accounting for 100% of the plurality of nanofibers.
[0081] Another embodiment of the present disclosure comprises a plurality of nanofibers having at least 50% to a maximum of 75% double-walled carbon nanotubes. The remainder are filled with single-walled and / or multi-walled carbon nanotubes, accounting for 100% of the plurality of nanofibers.
[0082] Another embodiment of the present disclosure comprises a plurality of nanofibers having at least 20% single-walled carbon nanotubes. The remainder are filled with double-walled and / or multi-walled carbon nanotubes, accounting for 100% of the plurality of nanofibers.
[0083] One embodiment of the present disclosure comprises a plurality of nanofibers having at least 50% to a maximum of 75% double-walled carbon nanotubes, 20% to 40% single-walled carbon nanotubes, and 1% or more multi-walled carbon nanotubes, which together account for 100% of the plurality of nanofibers.
[0084] One embodiment of the present disclosure further includes a simple and effective structural design as an alternative to address the mechanical strength requirements and hydrogen plasma etching resistance of the pellicle film.
[0085] An interconnected nanofiber network structure or pellicle film having multiple nanofibers and at least two different thicknesses corresponding to at least two different light transmittances is schematically illustrated in Figures 2 to 4. The pellicle film 200 in Figure 2 has a peripheral region (feature 210), a transition region (feature 220), and a central region (feature 230). The pellicle film 200 is further loaded onto a pellicle boundary 305 to produce the pellicle 300 in Figure 3, the pellicle also having a peripheral region (feature 310 corresponding to feature 210), a transition region (feature 320 corresponding to feature 220), and a central region (feature 330 corresponding to feature 230). Figure 4 is a cross-sectional view of the pellicle film 200. Figure 4 further illustrates and highlights a random but uniform distribution pattern of multiple intersecting interconnected nanofibers in a single-layer layout having at least two different thicknesses. It is preferable that lower light transmittances are assigned to the peripheral region of the pellicle film (feature 210 in Figure 2 and feature 310 in Figure 3, respectively). This peripheral region of the pellicle film may be further unused or not utilized during microchip production, and may or may not be required to meet all EUV pellicle requirements according to industry standards at the time. However, as part of the ultrathin film, this peripheral region is close to the frame and / or subject to additional mechanical stress due to the roughness of the frame edges, as well as additional thermal stress due to the accumulation and emission of EUV radiant energy by the frame. This can lead to faster etching than other areas of the film irradiated with EUV radiation due to the reflection and / or deflection of hydrogen plasma ions and radicals from the frame, causing premature failure of the pellicle film, including film rupture. Thickening the peripheral region or reducing the light transmittance in the peripheral region can extend the lifespan of the pellicle film. The interconnected nanofiber network structure or the central region of the pellicle film (features 230 in Figure 2 and 330 in Figure 3, respectively) may have higher light transmittance. This central region may meet most, if not all, of the subsequent EUV pellicle requirements.The central region may further preferably have EUV transmittances of at least 80%, 85%, 90%, 92%, 95%, and up to 99%. The variation in EUV transmittance, i.e., the difference between any two EUV transmittances within the central region, must be less than 2.0%, preferably less than 1.0%, or less than 0.4%. Uniform light transmittance (i.e., uniformity of the pellicle film) in this disclosure may include at least one of these low percentage (i.e., less than 2.0%, less than 1.0%, or less than 0.4%) EUV transmittance variation features. The central region may also have EUV scattering of less than 0.5%, or preferably less than 0.3%.
[0086] The lower light transmittance to the peripheral region of the pellicle film can be selected from a range of at least 40% to 96% based on 550nm wavelength measurements. The higher light transmittance to the central region of the pellicle film can be selected from a range of at least 80% to 99% based on 550nm wavelength measurements. Furthermore, the lower light transmittance should be less than the higher transmittance for a pellicle film having at least two light transmittances. Uniform light transmittance in this disclosure may further include the characteristic variation of the transmittance at 550nm wavelength measured at any two locations of the pellicle film having a value of less than 5%, preferably less than 1%.
[0087] Another embodiment of the present disclosure may include a transition region located between and joining a peripheral region and a central region (feature 220 in Figure 2 and feature 320 in Figure 3, respectively). A first edge of the transition region joins the peripheral region and may have all the properties of the peripheral region, including lower light transmittance, area density, and / or film thickness. A second opposite edge of the transition region joins the central region and may have all the properties of the peripheral region, including higher light transmittance, area density, and / or film thickness. For example, a change in the transition region with respect to one or more of its properties, such as light transmittance, area density, and / or film thickness, may occur gradually, forming a gradient from the first edge to the second edge. An exemplary light transmittance gradient is a linear gradient. Another exemplary light transmittance gradient includes at least a portion of the transition region having a linear gradient of light transmittance. Furthermore, another exemplary change in light transmittance with respect to the transition region is a variety of rates.
[0088] Another embodiment of the present disclosure includes visible light transmittance, which is selected from a range between a lower limit of 40% and an upper limit of 97% measured at a wavelength of 550 nm for at least two different transmittances. Films or portions of films with a transmittance of 98% or more at a wavelength of 550 nm may be too thin to handle and / or manufacture and may be very susceptible to external impacts. Films or portions of films with a transmittance of less than 40% at a wavelength of 550 nm may be too rigid and / or too brittle and may not provide the resilience to support another region of the film (e.g., the central region). At least one of the two 550 nm wavelength transmittances may preferably be 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 95%.
[0089] Another embodiment of the present disclosure includes one of at least two EUV transmittances of an interconnected nanofiber network structure, measured at a wavelength of 13.5 nm, selected or measured from a range of 80% to 99%. Regions of the interconnected nanofiber network that are useful for or designed for EUV exposure, such as the central region of a pellicle film, must satisfy EUV lithography requirements. An EUV transmittance of less than 80% may not satisfy such requirements. One or more of the at least two EUV transmittances may preferably be 85%, 90%, 92%, 95%, 97%, or 98%.
[0090] Another embodiment of the present disclosure includes a ratio of the higher transmittance to the lower transmittance among at least two transmittances in the visible and / or EUV wavelengths. This ratio has a lower limit of 2% and an upper limit of 50%, and preferred ratios are selected from 5%, 10%, 15%, 20%, 25%, 30%, 40%, or 45%.
[0091] EUV transmittance generally correlates non-linearly with visible light transmittance. This correlation can vary depending on the properties of the material being studied.
[0092] Another embodiment of the present disclosure involves the random and continuous dispersion of multiple carbon nanofibers or carbon nanotubes across an entire single layer of an interconnected nanofiber network structure or pellicle film having different or patterned light transmittances in all regions (see schematic diagram in Figure 4).
[0093] However, the embodiments of this disclosure are not limited to these, as different designs may be used.
[0094] Improvement of sagging Within an EUV scanner, the space between the EUV pellicle and the reticle is often very limited. Film deflection tests are frequently used to characterize the mechanical properties of EUV pellicle films, ensuring that the film functions as expected, within the limitations, maintaining air or gas flow under the scanner's pump-down and ventilation process, and not approaching or touching the photomask.
[0095] In a deflection test, air or a gas, preferably an inert gas such as argon or nitrogen, is applied perpendicularly to the film or pellicle film under a constant gas pressure (Pascals or Pa). For rectangular films, it is preferable that the flow of the test gas be directed towards a central spot on the film. The distance from the point of maximum film deformation under a predetermined constant gas pressure to the baseline of the film established without gas pressure is recorded; this is called the deflection distance. The applied gas pressure may continue to increase until the film bursts. The gas pressure that causes the film to burst is called the burst pressure. The deflection distance at the burst point of the film is called the deflection distance at the burst distance.
[0096] Figure 5 shows the deflection measurement results for three different full-size interconnected nanofiber network structures or pellicle films (i.e., films 10, 20, and 30 mounted on a boundary having an aperture of 110 mm × 140 mm), where the individual film deflection measurement results are shown by three curves, a solid line (feature 510), a dashed-dotted line (feature 520), and a double-dotted-dotted line (feature 530), respectively. Individual full-size interconnected nanofiber network structures having a size of at least 110 mm × 140 mm are disclosed as shown in Figure 5, and aspects of this disclosure are not limited thereto, as different sizes may be available.
[0097] The solid line in Figure 5 (feature 510) represents the deflection distance against gas pressure of a graph of film 10 having a single, uniform light transmittance (LTR) of 80%, measured at a wavelength of 550 nm.
[0098] The dashed line in Figure 5 (feature 520) represents the deflection distance of film 20 with respect to gas pressure according to one embodiment, the film having at least two LTRs, both measured at a wavelength of 550 nm, a uniform 50% LTR in its peripheral region with a width of 2.5 mm, a uniform 80% LTR in its central region, and a transition region connecting both the 80% and 50% LTR regions and having an LTR gradient from 80% LTR to 50% LTR. The dashed line in Figure 5 (feature 530) represents a graph of the deflection distance with respect to gas pressure of film 30 having a single, uniform 50% LTR measured at a wavelength of 550 nm. As illustrated in Figure 5, film 10 has the largest deflection, film 30 has the smallest deflection, and film 20 has a moderate deflection between them.
[0099] The embodiment in Figure 5 illustrates the advantages and benefits of the present disclosure and its embodiments. A pellicle film having at least two light transmittances (e.g., film 20) and deflection measurements corresponding to the dashed line 520 provides the same light transmission characteristics through its central region, including a high EUV transmittance with the higher light transmittance among the at least two light transmittances, as another pellicle film (e.g., film 10) having a uniform light transmittance equal to a higher light transmittance, while, more importantly, a pellicle film having a deflection measurement represented by the dashed line 520 (film 20) reduces deflection compared to another pellicle film having a single, uniform light transmittance equal to a higher light transmittance with its deflection measurement result represented by the solid line 510 (e.g., film 10). Film 20 results in greater mechanical strength of the film.
[0100] A pellicle film (film 20) having a deflection measurement indicated by the dashed line 520 has a higher film deflection than yet another pellicle film having a single uniform light transmittance equal to a deflection measurement indicated by the double dashed line 530, which has a lower light transmittance (film 30).
[0101] Furthermore, in the deflection test, the pellicle film will eventually rupture as the gas pressure continues to increase. At the time of rupture, the gas flow pressure is recorded as the pressure at rupture (or rupture pressure), the deflection is recorded as the deflection at rupture, and the flow rate is recorded as the flow rate at rupture.
[0102] Figure 6 lists the other test results for the three pellicle films described above (i.e., film 10, film 20, and film 30) along with the deflection measurement results shown in Figure 5 as a solid line (feature 510), a dashed line (feature 520), and a double dashed line (feature 530). The deflection test results in Figure 6, where a constant gas pressure of 2 Pascals (2 Pa) is applied, are snapshots of Figure 5. Film 20, represented by the dashed line (feature 520), has a lower deflection distance of 1.35 mm at 2 Pa and bursts at a higher gas pressure of 17.8 Pa. Compared to film 10, which has a deflection distance of 1.85 mm at 2 Pa, a burst pressure of 10.4 Pa, and a burst deflection distance of 4.01 mm under a weak gas flow of 5160 ml / min, film 20 has a higher burst deflection distance (or burst distance) of 4.42 mm when gas is administered at a higher flow rate of 8930 ml / min. The deflection distance of 4.42 mm at the time of rupture is even greater than the deflection distance of 3.22 mm at the time of rupture of film 30. This result indicates that film 20 may have the highest elasticity or the least brittleness among all three films tested.
[0103] These results further demonstrate the advantages of the present disclosure and its embodiments in improving the mechanical strength of interconnected nanofiber network structures or pellicle films while maintaining the same EUV pellicle requirements.
[0104] Hydrogen plasma etching resistance Embodiments of the present disclosure are further tested and demonstrated in exemplary hydrogen plasma etching experiments.
[0105] The etching experiment was defined and carried out as follows: a pellicle nanofiber film was placed in a sealed chamber, and a high-frequency energy of 80 watts at 13.56 MHz was applied for 20 seconds, while hydrogen gas was flowed through the chamber at a constant flow rate of 15 sccm. The results of the hydrogen plasma etching experiment are summarized in the table in Figure 7.
[0106] In Figure 7, samples A, B, C, and D (A-D) are exemplary interconnected and intersecting nanofiber network structures fabricated from a single carbon nanotube suspension by the exemplary filtration method described above. Samples A-D are all single-layer, self-supporting films. Each of samples A, B, C, and D covers a 10 mm × 10 mm frame aperture. Samples A and B have one uniform light transmittance (LTR) of 80% measured at a wavelength of 550 nm. Samples C and D have two LTRs measured at a wavelength of 550 nm, with 80% in the central region having a size of 5 mm × 5 mm and 50% in the periphery (excluding the 5 mm × 5 mm region). Samples B and D were treated by the hydrogen plasma etching method described above, while samples A and C were untreated.
[0107] Samples A to D were subjected to the deflection and bursting test as described above.
[0108] The burst pressure of sample B, measured at 181.0 Pa, is lower than the burst pressure of sample A (530.2 Pa), mainly due to hydrogen plasma etching, representing a 65.8% reduction in burst pressure compared to sample A. The burst pressure of sample D, measured at 354.9 Pa, is lower than the burst pressure of sample C (878.3 Pa), both of which have been hydrogen plasma etched, but have a 59.59% reduction in burst pressure. The difference in the percentage of burst pressure reduction, or the lower percentage decrease in burst pressure, demonstrates the advantage of one embodiment of the present disclosure, which is a double area density film and / or a double light transmission film, for example, that samples C and D contribute to stronger mechanical properties of the film compared to a single area density and / or a single light transmission film, and affirms this.
[0109] Furthermore, the bursting pressure of sample C, measured at 878.3 Pa, is higher than that of sample A (530.2 Pa) (a 65.65% enhancement), again demonstrating the advantage of the doubled area density and / or doubled light transmittance represented by sample C, which surpasses the single area density and / or single light transmittance of sample A.
[0110] The burst pressure value of sample D is twice that of sample B, i.e., 354.9 Pa compared to 181.0 Pa (a 96.08% enhancement). Embodiments having two area densities and / or two light transmittances, such as sample D, result in significant differences in the burst pressure of the nanofiber film.
[0111] In summary, intersecting and interconnected nanofiber films or pellicle films exhibit improved film mechanical strength and enhanced hydrogen plasma etching resistance. The examples of embodiments described herein are intended to provide a general understanding of various embodiments. The examples are not intended to serve as a complete description of all elements and features of the products and methods that make up the products or methods described herein. Many other embodiments may become apparent to those skilled in the art by examining this disclosure. Since other embodiments may be utilized and derived from this disclosure, structural and logical substitutions and modifications may be made without departing from the scope of this disclosure. Furthermore, the examples are merely representative and may not be depicted in any particular proportion. Some proportions in the examples may be exaggerated, while others may be minimized. Therefore, this disclosure and the figures should be considered illustrative, not limiting.
[0112] In this specification, one or more embodiments of this disclosure may be referred to individually and / or collectively by the term “Invention” merely for convenience and without the intention of spontaneously limiting the scope of this application to any particular invention or inventive concept. Furthermore, while specific embodiments have been illustrated and described herein, it should be recognized that any subsequent arrangement designed to achieve the same or similar objectives may be used instead of the specific embodiments shown. This disclosure is intended to cover all possible subsequent adaptations or variations of various embodiments. Combinations of the above embodiments and other embodiments not specifically described herein will become apparent to those skilled in the art upon examination of this description.
[0113] This abstract of the disclosure is submitted with the understanding that it is not to be used to interpret or limit the scope or meaning of the claims. In addition, in the preceding detailed description, various features may be grouped together or described in a single embodiment for the purpose of simplifying the disclosure. The disclosure should not be construed as reflecting an intention that the embodiments described in the claims require more features than are expressly stated in each claim. Rather, as reflected in the following claims, the subject matter of the invention may be directed to less than all of the features of any of the disclosed embodiments. Accordingly, the following claims are incorporated into a form for carrying out the invention, and each claim is independent as defining the subject matter that is individually claimed.
[0114] The subject matter disclosed above should be considered illustrative and not limiting, and the attached claims are intended to cover all such modifications, extensions, and other embodiments that fall within the true spirit and scope of this disclosure. Accordingly, to the maximum extent permitted by law, the scope of this disclosure should be determined by the broadest permissible interpretation of the following claims and their equivalents, and should not be limited or restricted by the prior detailed description.
Claims
1. A nanostructured film for extreme ultraviolet (EUV) lithography, The present invention comprises a plurality of carbon nanofibers that intersect randomly and continuously to form a first interconnected nanofiber network structure, wherein the first interconnected nanofiber network structure is A first surface oriented in a planar manner, Geometric shapes and, The target size of the aforementioned geometric shape is, The plurality of carbon nanofibers include single-walled carbon nanofibers, double-walled carbon nanofibers, and multi-walled carbon nanofibers. The geometric shape includes a central region having a first light transmittance and a peripheral region having a second light transmittance, wherein the peripheral region does not overlap with the first central region, and the second light transmittance is different from the first light transmittance. A nanostructured film in which the number of walls in the single-walled carbon nanofiber is 1, the number of walls in the double-walled carbon nanofiber is 2, and the number of walls in the multi-walled carbon nanofiber is 3 or more.
2. The nanostructured film according to claim 1, further comprising a transition region between the peripheral region and the central region, wherein the transition region connects the peripheral region to the central region, the transition region has a variable light transmittance, the variable light transmittance starts from the second light transmittance, the transition region connects to the peripheral region and ends at the first light transmittance, and the transition region connects to the central region.
3. The nanostructured film according to claim 2, wherein the variable light transmittance forms a flat descending gradient from the second light transmittance to the first light transmittance.
4. The nanostructured film according to claim 1, wherein the first light transmittance is higher than the second light transmittance.
5. The deflection of the first interconnected nanofiber network structure is smaller than the deflection of the second interconnected nanofiber network structure. The plurality of carbon nanofibers intersect randomly and continuously to form a second interconnected nanofiber network. The nanostructured film according to claim 4, wherein the second interconnected nanofiber network structure has the geometric shape, the target size, and a light transmittance equal to the first light transmittance.
6. The deflection of the first interconnected nanofiber network structure is greater than the deflection of the third interconnected nanofiber network structure. The plurality of carbon nanofibers intersect randomly and continuously to form a third interconnected nanofiber network. The nanostructured film according to claim 4, wherein the third interconnected nanofiber network structure has a uniform light transmittance equal to the geometric shape, the target size, and the second light transmittance.
7. The nanostructured film according to claim 1, wherein the plurality of carbon nanofibers include 50% or more double-walled carbon nanofibers.
8. The nanostructured film according to claim 7, wherein the plurality of carbon nanofibers include 50% to 75% double-walled carbon nanofibers.
9. The nanostructured film according to claim 7, wherein the plurality of carbon nanofibers further comprises 20% to 40% single-walled carbon nanofibers.
10. The nanostructured film according to claim 7, wherein the plurality of carbon nanofibers further comprises at least 1% multi-walled carbon nanofibers.
11. The aforementioned central region has an EUV transmittance of 80% or more, as described in claim 1, for the nanostructured film.
12. The aforementioned central region has an EUV transmittance of 90% or more, as described in claim 1, for the nanostructured film.
13. The aforementioned central region has an EUV transmittance of 92% or more, as described in claim 1, for the nanostructured film.
14. The aforementioned central region has an EUV transmittance of 95% or more, as described in claim 1, the nanostructured film.
15. The nanostructured film according to claim 1, wherein the geometric shape is rectangular, the peripheral region surrounds the central region, and the peripheral region has four connected straight sections.
16. The nanostructured film according to claim 15, wherein the second light transmittance of at least one of the four linear portions is higher than the first light transmittance of the central region.
17. The nanostructured film according to claim 15, wherein the target size of the geometric shape is 110 mm x 140 mm or larger.
18. The nanostructured film according to claim 5, wherein the bursting pressure of the first interconnected nanofiber network structure is higher than the bursting pressure of the second interconnected nanofiber network structure.
19. A method for performing extreme ultraviolet (EUV) lithography, comprising transmitting EUV irradiation through a pellicle, The pellicle has a pellicle boundary having an aperture, The invention comprises at least one layer of multiple carbon nanofibers that intersect randomly and continuously to form an interconnected nanofiber network structure, wherein the interconnected nanofiber network structure is mounted on the pellicle boundary to cover the aperture, and the interconnected nanofiber network structure Surfaces in a planar orientation, A central region having a first light transmittance, A method for performing extreme ultraviolet (EUV) lithography, comprising a peripheral region, wherein the peripheral region is divided into four connected linear portions surrounding the central region, at least one of the four connected linear portions having a second light transmittance lower than the first light transmittance, and the central region having an EUV transmittance of at least 80%.
20. The method according to claim 19, wherein the first interconnected nanofiber network structure further includes a transition region between the peripheral region and the central region, the transition region having a light transmittance gradient having a light transmittance gradient transitioning from the second light transmittance, and the transition region is connected to at least one of the four connected linear portions of the peripheral region.
21. The method according to claim 19, wherein the aperture is rectangular and has a target size of 110 mm x 140 mm or more.
22. The method according to claim 20, wherein the transition region has a portion of the transition region having a linear light transmittance gradient.